Cured epoxy resin compositions suitable for electronic device enclosures, articles, and methods

JP7624835B2Active Publication Date: 2025-01-313M INNOVATIVE PROPERTIES CO
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2020536144
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2017-12-27
Filing Date
2018-12-21
Publication Date
2025-01-31
Estimated Expiration
2038-12-21

Smart Images

  • Figure 0007624835000016
    Figure 0007624835000016
  • Figure 0007624835000017
    Figure 0007624835000017
  • Figure 0007624835000018
    Figure 0007624835000018
Patent Text Reader

Abstract

An electronic device is described that includes an enclosure, the enclosure comprising a cured epoxy resin composition including at least 50% by volume of electrically non-electrically and thermally conductive inorganic particles, the inorganic particles being selected from alumina, boron nitride, silicon carbide, alumina trihydrate, and mixtures thereof. The enclosure may be a housing for a phone, laptop, or mouse. Alternatively, the enclosure may be a case for the electronic device. Methods for making the epoxy resin composition and the enclosure for the electronic device are also described.
Need to check novelty before this filing date? Find Prior Art

Description

Summary of the Invention

[0001] In one embodiment, an electronic device is described that includes an enclosure, the enclosure comprising a cured epoxy resin composition that includes at least 50% by volume of non-electrically conductive, thermally conductive inorganic particles. The enclosure may be a housing for a phone, laptop, or mouse. Alternatively, the enclosure may be a case for the electronic device.

[0002] In another embodiment, an epoxy resin composition is described that includes an organic component that includes a first portion including an epoxy resin and a second portion including 2-20 wt. % of an epoxy reactive oligomeric or polymeric moiety having a glass transition temperature below 0° C., and at least 50 vol. % of electrically non-conductive, thermally conductive inorganic particles.

[0003] In another embodiment, an epoxy resin composition is described that includes an organic component comprising a first portion including an epoxy resin and a second portion including an epoxy-reactive oligomeric or polymeric portion having a glass transition temperature less than 0° C., and at least 50 volume % of non-electrically conductive, thermally conductive inorganic particles, wherein the epoxy resin material has a glass transition temperature less than 100° C. after curing.

[0004] In another embodiment, a method of making an enclosure for an electronic device is described that includes providing an epoxy resin composition described herein and molding the composition into a housing or case. In one embodiment, the molding step includes providing the epoxy resin composition in a mold and curing the epoxy resin composition. [Brief description of the drawings]

[0005] [Figure 1] FIG. 2 is a schematic perspective view of a case for an electronic device. [Diagram 2] FIG. 2 is a perspective view of a housing of an electronic device. [Diagram 3]1 is a plot of tan δ as a function of temperature for various embodied cured epoxy resin compositions. [Figure 4] 1 is a plot of tan δ as a function of temperature for various embodied cured epoxy resin compositions. [Diagram 5] 1 is a plot of tan δ as a function of temperature for various embodied cured epoxy resin compositions. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0006] Described herein are enclosures (e.g., housings or cases) for electronic devices that include a cured epoxy resin composition. Curable epoxy resin compositions are also described.

[0007] 1, the embodied exemplary case 100 (case 100) is three-dimensional and includes an inner major surface 110 generally parallel to an outer major surface (not shown), and a sidewall 115. The case is shaped and sized to receive and fit an electronic device 120. Case 100 typically includes an opening 101. A camera lens and flash of electronic device 120 are typically exposed through opening 101. Alternatively, opening 101 may further include a sufficiently transparent film such that case 100 and cover 120 form a waterproof enclosure for electronic device 120. Case 100 may optionally include a cover 120 including a sufficiently transparent film 125 such that a display 130 of electronic device 120 can be viewed through film 125. In some embodiments, the entire case 100 includes a cured epoxy resin composition as described herein. A frame 121 of cover 120 may also include a cured epoxy resin composition as described herein. In some embodiments, only a portion of the case includes a cured epoxy resin composition as described herein. In some embodiments, the case, or a portion thereof, is in electrical communication with the battery such that the battery can be charged through the case.

[0008] 1 and 2, the embodied exemplary housings 200 and 220 (housings 200 and 220) are three-dimensional and generally include an inner major surface 210 parallel to an outer major surface (not shown), and a sidewall 215. Housings 200 and 220 typically form the back of an electronic device. Housing 220 is attached to a front (e.g., display surface) 130 of electronic device 120. Electronic components (not shown) (e.g., batteries, circuitry, computer chips, etc.) are disposed between the front (e.g., display surface) 130 of electronic device 120 and housing 220. Housings 200 and 220 typically include a camera lens 205 and a flash 206 integrated within the housing. In some embodiments, the entire housing 200 includes a cured epoxy resin composition as described herein. In other embodiments, only a portion of the housing includes a cured epoxy resin composition as described herein. In some embodiments, the housing or a portion thereof is in electrical communication with a battery such that the battery can be charged through the case.

[0009] The epoxy resin compositions described herein are suitable for use as enclosures (e.g., cases and / or housings) for various electronic devices. Exemplary electronic devices include mobile phones, table computers, laptop computers, and battery-operated accessories such as remote mice.

[0010] Epoxy resin compositions generally include at least one epoxy resin that contains at least two epoxide groups. Epoxide groups are cyclic ethers with three ring atoms, sometimes also called glycidyl or oxirane groups. Epoxy resins are low molecular weight monomers that are typically liquid at ambient temperature.

[0011] The epoxy resin composition generally comprises at least one epoxy resin that includes at least one cyclic moiety, which may be aromatic or cycloaliphatic.

[0012] In some embodiments, the epoxy resin composition comprises a bisphenol epoxy resin formed from reacting epichlorohydrin with bisphenol A to form a diglycidyl ether of bisphenol A.

[0013] Examples of commercially available bisphenol epoxy resins include diglycidyl ethers of bisphenol A (e.g., those available under the trade names EPON 828, EPON 1001, EPON 1004, EPON 2004, EPON 1510, and EPON 1310 from Momentive Specialty Chemicals, Inc., and those available under the trade names DER 331, DER 332, DER 334, and DEN 439 from Dow Chemical Co.); diglycidyl ethers of bisphenol F (e.g., those available under the trade name ARALDITE GY 281 from Huntsman Corporation) or blends of bisphenol A and F resins (e.g., EPIKOTE 232 from Momentive Specialty Chemicals, Inc.); flame retardant epoxy resins (e.g., those available under the trade name DER 560, and brominated bisphenol type epoxy resins such as those available from Dow Chemical Company).

[0014] Aromatic epoxy resins can also be prepared by the reaction of aromatic alcohols, such as biphenyl diols and triphenyl diols and triols, with epichlorohydrin. Such aromatic biphenyl and triphenyl epoxy resins are not bisphenol epoxy resins. One representative compound is a tris-(hydroxylphenyl)methane based epoxy available as Tactix™ 742 from Huntsman Corporation, Basel, Switzerland.

[0015] Novolac epoxy resins are formed by the reaction of phenol with formaldehyde, followed by glycidylation with epichlorohydrin to produce epoxidized novolacs such as epoxy phenol novolacs (EPN) and epoxy cresol novolacs (ECN). These are very viscous to solid resins and have a typical average epoxide functionality of about 2 to 6. A representative commercially available novolac epoxy resin is a semi-solid epoxy novolac resin available from Dow under the trade name "DEN431". Such novolac epoxy resins can be used in combination with epoxy resins that are liquid at 25°C.

[0016] Preferred epoxy resins are cycloaliphatic epoxy resins containing two or more 1,2 epoxy groups per molecule, which are generally prepared by epoxidizing unsaturated aromatic hydrocarbon compounds, such as cycloolefins, using hydrogen peroxide or peracids, such as peracetic acid and perbenzoic acid, as known in the art.

[0017] Such cycloaliphatic epoxy resins have a saturated (i.e., non-aromatic) ring structure, with the epoxide groups either being part of the ring or attached to the ring structure. These epoxy resins typically contain one or more ester linkages between the epoxide groups. An alkylene (C1-C4) bond is also typically present between the epoxide groups and the ester linkages or between the ester linkages.

[0018] One preferred cycloaliphatic epoxy resin is 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate, shown below: [ka]

[0019] Another preferred exemplary cycloaliphatic epoxy resin is bis(3,4-epoxycyclohexylmethyl)adipate, shown as follows: [ka]

[0020] Other suitable cycloaliphatic epoxy resins include vinylcyclohexane dioxide, which contains two epoxide groups (one of which is part of a ring structure); 3,4-epoxy-6-methylcyclohexylmethyl-3,4-epoxycyclohexanecarboxylate, and dicyclopentadiene dioxide.

[0021] Other suitable cycloaliphatic epoxy resins containing glycidyl ethers include 1,2-bis(2,3-epoxycyclopentyloxy)-ethane; 2,3-epoxycyclopentyl glycidyl ether; diglycidyl cyclohexane-1,2-dicarboxylate; 3,4-epoxycyclohexyl glycidyl ether; bis-(2,3-epoxycyclopentyl)ether; bis-(3,4-epoxycyclohexyl)ether; 5(6)-glycidyl-2-(1,2-epoxyethyl)bicyclo[2.2.1]heptane; cyclohexa-1,3-diene dioxide; and 3,4-epoxy-6-methylcyclohexylmethyl 3',4'-epoxy-6'-methylcyclohexanecarboxylate.

[0022] Also suitable are epoxy resins in which the 1,2-epoxy groups are bonded to various heteroatoms or functional groups, such as, for example, N,N,O-triglycidyl derivatives of 4-aminophenol, N,N,O-triglycidyl derivatives of 3-aminophenol, glycidyl ethers / esters of salicylic acid, N-glycidyl-N'-(2-glycidyloxypropyl)-5,5-dimethylhydantoin, or 2-glycidyloxy-1,3-bis-(5,5-dimethyl-1-glycidylhydantoin-3-yl)propane.

[0023] The epoxy resin typically has an epoxy equivalent weight of 50 to 250, 300, 350, 400, 450, or 500 grams per epoxide group. The epoxy resin typically has a viscosity of less than about 1000 cps at 25° C. In some embodiments, the viscosity is at least 50, 100, 150, 200, 250, or 300 centipoise. In some embodiments, the viscosity is no greater than 900, 800, 700, 600, or 500 centipoise. A single epoxy resin or a combination of epoxy resins may be utilized. The epoxy resin composition typically includes at least 5, 6, 7, 8, 9, or 10 weight percent epoxy resin, based on the weight of the total epoxy resin composition. Due to the high concentration of thermally conductive inorganic particles, the amount of epoxy resin is typically no greater than 20 weight percent, and in some embodiments, no greater than 19, 18, 17, 16, or 15 weight percent.

[0024] In some embodiments, the epoxy resin composition further comprises an oligomeric or polymeric component. The oligomeric or polymeric component can impart flexibility, thermal shock resistance, crack resistance, and impact resistance to the cured epoxy resin composition. Unless otherwise specified, glass transition temperature (Tg) refers to a glass transition temperature determined according to the test method described in the Examples. The oligomeric or polymeric component generally has a glass transition temperature (Tg) of less than 0°C. In some embodiments, the glass transition temperature of the oligomeric component is less than -20°C, -30°C, -40°C, -50°C, -60°C. The glass transition temperature of the oligomeric component is typically at least -80°C or -70°C. The glass transition temperatures of various homopolymers are reported in the literature. The glass transition temperatures of various copolymers are also reported in the literature or can be estimated using the Fox equation.

[0025] In some embodiments, the oligomeric or polymeric component is a toughening agent, an epoxy-reactive oligomeric or polymeric component, or a combination thereof. The epoxy resin composition may include at least one toughening agent and at least one epoxy-reactive oligomeric or polymeric component, two or more toughening agents, or two or more epoxy-reactive oligomeric and / or polymeric components.

[0026] The glass transition temperature of the epoxy resin in the absence of an oligomeric or polymeric component is greater than 100° C. In some embodiments, the glass transition temperature of the epoxy resin in the absence of an oligomeric or polymeric component is at least 110° C., 120° C., 130° C., 140° C., or 150° C. The glass transition temperature of the epoxy resin in the absence of an oligomeric or polymeric component is typically no greater than 300° C., 275° C., 250° C., 225° C., 200° C., or 175° C.

[0027] When the oligomeric or polymeric component is a toughening agent, the glass transition of the epoxy resin composition containing the toughening agent may be in the same range as the epoxy resin alone. In some embodiments, the inclusion of the toughening agent can reduce the Tg of the epoxy resin composition by 10, 20, 30, 40, or 50° C. or more relative to the epoxy resin alone. In some embodiments, for example, when an epoxy reactive oligomeric and / or polymeric component is utilized, the cured epoxy resin composition has a Tg of less than 140, 135, or 130° C. In some embodiments, the cured epoxy resin composition has a Tg of less than 125, 120, 115, 110, 105, or 100° C. In some embodiments, the cured epoxy resin composition has a Tg of less than 100° C. In some embodiments, the cured epoxy resin composition has a Tg of at least 50, 55, 60, 65, 70, 75, 80, 85, 90, or 100° C.

[0028] In some embodiments, the cured epoxy resin composition has a single glass transition temperature as shown in Figure 3. For example, in one embodiment, when the epoxy resin composition includes an oligomeric or polymeric portion (e.g., polycaprolactone) and the dispersant includes a portion that is miscible with the oligomeric or polymeric portion (e.g., polycaprolactone), the cured epoxy resin may have a single Tg. When the cured epoxy resin composition has a single Tg, the tan δ peak is typically relatively narrow. For example, the tan δ peak half-width is 50°C or less.

[0029] In another embodiment, the cured epoxy resin composition has at least two glass transition temperatures as shown in FIG.

[0030] In another embodiment, the cured epoxy resin composition may exhibit a single or multiple Tg in combination with a relatively broad tan δ peak as shown in Figure 5. In this embodiment, the tan δ peak half-width is greater than 50°C. For example, in some embodiments, the tan δ peak half-width is at least 55, 60, 65, 70, 75, 80, 85, or 90°C. The tan δ peak half-width is typically no greater than 125, 120, 115, or 110°C.

[0031] The epoxy resin composition typically comprises at least 1, 1.5, 2, or 2.5 wt.% of the oligomeric and / or polymeric component, based on the weight of the total epoxy resin composition. The amount of the oligomeric and / or polymeric component is typically no more than 20, 19, 18, 17, 16, or 15 wt.%. In some embodiments, the amount of the oligomeric and / or polymeric component is no more than 14, 13, 12, 11, or 10 wt.%.

[0032] The weight ratio of the epoxy resin to the oligomer and / or polymer component can vary. Typically, the weight of the epoxy resin is equal to or greater than the amount of the oligomer and / or polymer component. The weight ratio of the epoxy resin to the oligomer and / or polymer component can range from 1:1 to 10:1. In some embodiments, the weight ratio of the epoxy resin to the oligomer and / or polymer component is at least 1.1:1, 1.2:1, 1.3:1, 1.4:1, or 1.5:1. In some embodiments, the weight ratio of the epoxy resin to the oligomer and / or polymer component is 7:1 or 6:1 or 5:1 or 4:1 or 3:1 or less.

[0033] In some embodiments, the oligomeric or polymeric component can be characterized as a toughening agent. Toughening agents are typically organic polymeric additives that phase separate in the cured epoxy resin. Toughening agents can be characterized as non-reactive oligomeric or polymeric components. Toughening agents can include, for example, block copolymers, amphiphilic block copolymers, acrylic block copolymers, carboxyl-terminated butadiene acrylonitrile rubbers (CTBN), core-shell rubbers (CSR), linear polybutadiene-polyacrylonitrile copolymers, oligomeric polysiloxanes, silicone polyethers, organopolysiloxane resins, or mixtures thereof.

[0034] Other epoxy reactive polymer toughening agents include carboxyl terminated polybutadiene, polysulfide based toughening agents, amine terminated butadiene nitrile rubber, polythioethers, or mixtures thereof.

[0035] The amphiphilic polyether block copolymer toughening agents include one or more polyether block copolymers comprising at least one epoxy-miscible polyether block segment derived from an alkylene oxide, such as ethylene oxide (EO), and at least one epoxy-immiscible polyether block segment derived from an alkylene oxide, such as 1,2-epoxybutane, commonly known as butylene oxide (BO). The immiscible block segment may also be composed of a mixture of C3 or higher carbon number analog monomers that copolymerize to provide the immiscible block segment.

[0036] Examples of epoxy resin-compatible polyether block segments include polyethylene oxide blocks, propylene oxide blocks, poly(ethylene oxide-co-propylene oxide) blocks, poly(ethylene oxide-ran-propylene oxide) blocks, or mixtures thereof. Preferably, the epoxy resin-compatible polyether block segments useful in the present invention may be polyethylene oxide blocks.

[0037] Examples of epoxy resin immiscible polyether block segments include polybutylene oxide blocks, polyhexylene oxide blocks derived from 1,2-epoxyhexane, polydodecylene oxide blocks derived from 1,2-epoxydodecane, or mixtures thereof. Preferably, the epoxy resin immiscible polyether block segments useful in the present invention may be polybutylene oxide blocks.

[0038] Amphiphilic polyether block copolymer toughening agents include, for example, but are not limited to, diblock copolymers, linear triblock, linear tetrablock, other multiblock structures, branched block structures, or star block structures.

[0039] Examples of amphiphilic polyether diblock copolymer toughening agents include poly(ethylene oxide)-b-poly(butylene oxide) (PEO-PBO) or amphiphilic polyether triblock copolymers such as poly(ethylene oxide)-b-poly(butylene oxide)-b-poly(ethylene oxide) (PEO-PBO-PEO).

[0040] In another embodiment, the epoxy resin composition comprises an epoxy-reactive oligomer component that contains a relatively small number of repeating units compared to typical polymers. The weight average molecular weight of the epoxy-reactive oligomer component is typically at least 150, 200, 150, 300, 350, 400, 450, or 500 g / mol. In some embodiments, the weight average molecular weight of the oligomer component is 10,000, 9,000, 8,000, 7,000, or 6,000 g / mol or less, and in some embodiments, 5,000, 4,500, 4,000, 3,500, 3,000, 2,500, 2,000, 1,500, or 1,000 g / mol or less. The oligomeric toughening agent may also have a molecular weight within this range. In other embodiments, the polymeric toughening agent may have a higher molecular weight, ranging up to 1,000,000 g / mol or 2,000,000 g / mol or more. For example, if the polymeric toughening agent is a crosslinked thermoset, the molecular weight may be too high to measure using conventional techniques. In some embodiments, the polymeric toughening agent has a weight average molecular weight of 500,000, 400,000, 300,000, or 200,000 g / mole or less.

[0041] In some embodiments, the epoxy reactive oligomer component has a melting point of no more than 30° C. or 25° C. The melting point is typically at least about 0° C., 5° C., or 10° C.

[0042] In some embodiments, the epoxy reactive oligomer component is a linear or branched polyester diol derived from caprolactone. Polycaprolactone (PCL) homopolymer is a biodegradable polyester with a low melting point of about 60° C. and a glass transition temperature of about −60° C. PCL can be prepared by ring-opening polymerization of ε-caprolactone using a catalyst such as stannous octoate, as is known in the art.

[0043] One suitable linear polyester diol derived from caprolactone is Capa™ 2054, which is reported to have a hydroxyl number of 200-215 mg KOH / g and a melting point of 18-23°C.

[0044] Another suitable trifunctional polyol is Dow TONE™ 301 polyol, which is reported to have a hydroxyl number of 561 and a melting point of 0-24°C.

[0045] In some embodiments, the oligomeric component can be characterized as a semi-crystalline component.

[0046] "Crystalline" means that the material exhibits a crystalline melting point at or above 20°C when measured in composition by differential scanning calorimetry (DSC). The peak temperature of the measured endotherm is taken as the crystalline melting point. The crystalline phase comprises a plurality of lattices in which the material adopts a conformation in which a highly regular arrangement of adjacent chemical moieties of which the material is composed is observed. The packing structure (close-packed arrangement) within the lattice is highly regular in both its chemical and geometrical aspects.

[0047] Semicrystalline components typically contain long segments of polymer chains that appear in both amorphous and crystalline states or phases above 20°C. The amorphous phase is considered to be a mass of randomly entangled polymer chains. The X-ray diffraction pattern of an amorphous polymer is a diffuse halo indicating that the polymer structure is not ordered. Amorphous polymers exhibit softening behavior at the glass transition temperature, but do not exhibit true melting or first order transitions. Materials in the semicrystalline state exhibit a characteristic melting point, above which the crystalline lattice becomes disordered and rapidly loses its identity. The X-ray diffraction patterns of such "semicrystalline" materials are generally distinguished by either concentric rings or a symmetric array of spots, which indicate the nature of crystalline order.

[0048] Examples of other epoxy-reactive oligomeric components include, for example, fatty acids, fatty acid anhydrides such as polyazelaic anhydride and dodecenylsuccinic anhydride, diols such as ethylene glycol, polyols, polyether diols such as polymers of ethylene glycol, polyethylene glycol and polypropylene glycol, aliphatic alcohols, and other materials having hydroxyl, carboxyl epoxy, and / or carboxylic anhydride functionality. Other suitable oligomeric components include trivalent and divalent carboxyl-, carboxylic anhydride-, glycidyl-, and hydroxyl-terminated polyethylene glycols, polypropylene glycols, or polybutylene glycols.

[0049] In some embodiments, the epoxy resin composition comprises a bisphenol epoxy resin that includes a flexible backbone. One representative structure is as follows: [ka] [wherein the large central block represents the oligomeric segment and the small blocks represent optional polar segments]. One representative bisphenol epoxy resin containing a flexible backbone is commercially available from DEC Corporation (Japan) under the trade name "EPICLON EXA 4850-150". In this embodiment, the oligomeric component can be characterized as an epoxy-reactive component that is pre-reacted with the epoxy resin.

[0050] In some embodiments, the viscosity of the flexible backbone bisphenol epoxy resin is less than 50,000, 45,000, 40,000, 35,000, 30,000, or 25,000 cps at 25° C. The viscosity is typically at least 5,000 cps at 25° C. In some embodiments, the molecular weight of the flexible backbone bisphenol epoxy resin is at least 200, 250, or 350 g / mol. In other embodiments, the molecular weight of the flexible backbone bisphenol epoxy resin is at least 400, 500, 600, or 700 g / mol. In yet other embodiments, the molecular weight of the flexible backbone bisphenol epoxy resin is at least 750, 800, or 900 g / mol. The molecular weight is typically no greater than 2000 or 1500 g / mol.

[0051] Other suitable epoxy-reactive oligomer components include those represented by the general formula: [ka] [wherein n is an integer of 10 to 300] may be mentioned.

[0052] Other suitable epoxy-reactive oligomeric components include carboxyl-, hydroxyl-, mercapto-, or glycidyl ether-terminated copolymers based on butadiene and a polar ethylenically unsaturated comonomer. One suitable epoxidized butadiene prepolymer having an average molecular weight of about 1200-1300 is commercially available as Poly Bd 605 from Elf Atochem North America Inc.

[0053] The epoxy resin composition optionally includes a curing agent. Common classes of curing agents for epoxy resins include amines, amides, ureas, imidazoles, and thiols. Curing agents are typically highly reactive with epoxide groups at ambient temperatures.

[0054] In some embodiments, the curing agent comprises a reactive -NH group or a reactive -NR1R2 group, where R1 and R2 are independently H or C1-C4 alkyl, most typically H or methyl.

[0055] Some classes of curing agents are primary, secondary, and tertiary polyamines. The polyamine curing agents may be linear, branched, or cyclic. In some preferred embodiments, the polyamine crosslinking agent is aliphatic. Alternatively, aromatic polyamines can be utilized.

[0056] Useful polyamines have the general formula R5-(NR1R2) x where R1 and R2 are independently H or alkyl, R5 is a polyvalent alkylene or arylene, and x is at least 2. The alkyl groups of R1 and R2 are typically C1-C 18 R1 and R2 may combine to form a cyclic amine. In some embodiments, x is 2 (i.e., a diamine). In other embodiments, x is 3 (i.e., a triamine). In yet other embodiments, x is 4.

[0057] Useful diamines have the general formula: [ka] where R1, R2, R3, and R4 are independently H or alkyl, and R5 is a divalent alkylene or arylene. In some embodiments, R1, R2, R3, and R4 are each H, and the diamine is a primary amine. In other embodiments, R1 and R4 are each H, R2 and R4 are each independently alkyl, and the diamine is a secondary amine. In yet other embodiments, R1, R2, R3, and R4 are independently alkyl, and the diamine is a tertiary amine.

[0058] In some embodiments, primary amines are preferred.Examples include hexamethylenediamine; 1,10-diaminodecane; 1,12-diaminododecane; 2-(4-aminophenyl)ethylamine; isophoronediamine; norbornanediamine, 4,4'-diaminodicyclohexylmethane; and 1,3-bis(aminomethyl)cyclohexane.Exemplary 6-membered ring diamines include, for example, piperazine and 1,4-diazabicyclo[2.2.2]octane ("DABCO").

[0059] Other useful polyamines include those having at least three amino groups, which may be primary, secondary, or a combination thereof. Examples include 3,3'-diaminobenzidine and hexamethylenetriamine.

[0060] Common curing agents used to cure cycloaliphatic epoxy resins include anhydrides derived from carboxylic acids having at least one anhydride group. Such anhydride curing agents are described in U.S. Patent No. 6,194,024, which is incorporated herein by reference.

[0061] In some embodiments, for example, when a toughening agent is utilized rather than an epoxy reactive oligomer component, the curing agent may be used in an amount that constitutes from about 20% to about 120%, preferably from about 80 to 110%, of the epoxy resin on an equivalent basis, and preferably from about 75% to about 100% of the epoxide equivalent.

[0062] However, when an epoxy-reactive oligomeric component is utilized, the (e.g., hydroxyl-functional) epoxy-reactive component can act as a curing agent. In this embodiment, the epoxy resin composition may contain a curing agent in an amount less than 20%, 15%, 10%, 5% of the epoxide equivalent.

[0063] In some embodiments, the epoxy resin composition further comprises a catalyst. Suitable catalysts for epoxy resins include, for example, tertiary amines, and acid catalysts such as octoate tin and antimony hexafluoride, and imidazole. Other suitable catalysts are fully substituted compounds including quaternary ammonium hydroxides and halides; quaternary phosphonium halides; arsine, amine oxides; aminophenols; phosphine oxides; phosphines; phosphonium halides; amines; phosphoramides; phosphine amines; and tertiary aminophenols. Mixtures of catalysts are also suitable.

[0064] The catalyst concentration is typically less than about 3, 2.5, 2, 1.5, or 1 weight percent, based on the weight of the total epoxy resin composition. In some embodiments, the amount of catalyst is at least 0.005, 0.01, 0.025, 0.05, or 0.1 weight percent.

[0065] The epoxy resin composition includes thermally conductive inorganic particles. Generally, the type and loading level of the inorganic particles are selected to provide a desired thermal conductivity. In some embodiments, the thermal conductivity of the cured epoxy resin composition (as determined by the test method described in the Examples) is at least 0.90, 0.95, or 1.0 W / m·K. In some embodiments, the thermal conductivity of the cured epoxy resin composition is at least 1.10, 1.15, or 1.20 W / m·K. In some embodiments, the thermal conductivity of the cured epoxy resin composition is no greater than 3.0, 2.9, 2.8, 2.7, 2.6, 2.5, 2.4, 2.3, 2.3, 2.1, or 2.0 W / m·K.

[0066] In some embodiments, the cured epoxy resin compositions are sufficiently conductive that electronic devices, including batteries, can be charged through an enclosure (e.g., a housing and / or case) that contains such cured epoxy resin compositions, and the inclusion of thermally conductive inorganic particles causes the cured epoxy resin compositions to be cool to the touch and resemble a ceramic rather than a plastic material.

[0067] The epoxy resin composition comprises more than 45% by volume of thermally conductive particles, based on the total volume of the epoxy composition. In some embodiments, the amount of thermally conductive inorganic filler is at least 46, 47, 48, 49, or 50% by volume. The amount of thermally conductive inorganic filler is typically no more than 75, 74, 73, 72, 71, 70, 69, 68, 67, 66, 65, 64, 63, 62, 61, or 60% by volume, based on the total volume of the epoxy composition.

[0068] Due to the relatively high concentration of thermally conductive particles, the cured epoxy resin composition can have a higher density. For example, as evidenced by Comparative Examples 1 and 2 below, a composition without thermally conductive particles can have a density ranging from about 1.1 g / cc to about 1.3 g / cc. Comparative Example 3, which contains 45 vol.% thermally conductive particles, has a density of 2.29 g / cc. However, the exemplified compositions have a density greater than 2.29 g / cc. In some embodiments, the cured epoxy resin composition has a density of at least 2.30, 2.31, 2.32, 2.33, 2.34, 2.35, 2.36, 2.37, 2.38, 2.39, or 2.40 g / cc. In some embodiments, the cured epoxy resin composition has a density of at least 2.41, 2.42, 2.43, 2.44, 2.45, 2.46, 2.47, 2.48, 2.49, or 2.50 g / cc. In some embodiments, the cured epoxy resin composition has a density less than or equal to 2.65, 2.64, 2.63, 2.62, 2.61, or 2.60 g / cc.

[0069] The thermally conductive inorganic particles are preferably non-conductive materials. Suitable non-conductive thermally conductive materials include ceramics such as metal oxides, hydroxides, oxyhydroxides, silicates, borides, carbides, and nitrides. Suitable ceramic fillers include, for example, silicon oxide, aluminum oxide, aluminum trihydroxide (ATH), boron nitride, silicon carbide, and beryllium oxide. Such materials are not electrically conductive, i.e., have an electronic band gap greater than 0 eV, in some embodiments at least 1, 2, 3, 4, or 5 eV. In some embodiments, such materials have an electronic band gap of 15 or 20 eV or less. The epoxy resin composition may optionally further include a small concentration of thermally conductive particles having an electronic band gap less than 0 eV or greater than 20 eV.

[0070] In a preferred embodiment, the thermally conductive particles comprise a material having a bulk thermal conductivity of >10 W / m·K. The thermal conductivities of some representative inorganic materials are set forth in the table below.

[0071] [Table 1]

[0072] In some embodiments, the thermally conductive particles include a material having a bulk thermal conductivity of at least 15 or 20 W / m·K. In other embodiments, the thermally conductive particles include a material having a bulk thermal conductivity of at least 25 or 30 W / m·K. In yet other embodiments, the thermally conductive particles include a material having a bulk thermal conductivity of at least 50, 75, or 100 W / m·K. In yet other embodiments, the thermally conductive particles include a material having a bulk thermal conductivity of at least 150 W / m·K. In an exemplary embodiment, the thermally conductive particles include a material having a bulk thermal conductivity of about 350 or 300 W / m·K or less.

[0073] Thermally conductive particles are available in a number of shapes, for example, spherical, irregular, plate-like, and needle-like. Thermally conductive particles generally have an aspect ratio of less than 100:1, 75:1, or 50:1. In some embodiments, thermally conductive particles have an aspect ratio of less than 3:1, 2.5:1, 2:1, or 1.5:1. In some embodiments, generally symmetrical (e.g., spherical or hemispherical) particles may be used.

[0074] In some embodiments, the median particle size d(0.50) of the thermally conductive particles is less than 100, 90, 80, 70, 60, 50 microns. In some embodiments, the particle size d(0.50) of the thermally conductive particles is less than 40, 35, 30, 25, 20, 15 microns. In some embodiments, the particle size d(0.50) of the thermally conductive particles is less than 10, 5, or 1 micron. In some embodiments, the particle size d(0.50) of the thermally conductive particles is at least 10, 15, 20, or 25 nanometers. In some embodiments, the particle size d(0.50) of the thermally conductive particles is at least 50, 75, 100, 125, 150, or 200 nanometers. In some embodiments, the particle size d(0.50) of the thermally conductive particles is at least 500 nm, 750 nm, 1 micron, 2 microns, or 3 microns. Particle size is often reported by the manufacturer of the thermally conductive particles. The cured epoxy resin can be subjected to pyrolysis and the particle size can be measured utilizing ASTM B822-17 "Standard Test Method for Particle Size Distribution of Metal Powders and Related Compounds by Light Scattering."

[0075] In typical embodiments, particle size refers to the "primary particle size" and means the median size of a single (non-aggregated, non-agglomerated) particle. Primary particles may form "agglomerates", i.e., weak associations between primary particles that may be held together by charge or polarity and are decomposable into smaller components. These weakly bound agglomerates typically break down during high energy mixing processes.

[0076] In some embodiments, the epoxy resin composition includes thermally conductive particles of different sizes and / or includes thermally conductive particles of different materials.

[0077] In some embodiments, the epoxy resin composition includes one or more dispersants. In general, dispersants may act to stabilize inorganic filler particles in compositions without dispersants, and particles may aggregate. Suitable dispersants may depend on the specific identity and surface chemistry of the thermally conductive particles. In some embodiments, suitable dispersants according to the present disclosure may include at least a binding group and a compatibilizing segment. The binding group may be ionically bonded to the particle surface. Examples of binding groups for alumina particles include phosphates, phosphonates, sulfonic acids, carboxylic acids, and amines. The compatibilizing segment may be selected to be miscible with the curable matrix. For epoxy resins, useful compatibilizers may include polyalkylene oxides, such as polypropylene oxide, polyethylene oxide, and polycaprolactone, and combinations thereof. Commercially available examples include BYK W-9010 (BYK Additives and Instruments), BYK W-9012 (BYK Additives and Instruments), Disberbyk 180 (BYK Additives and Instruments), and Solplus D510 (Lubrizol Corporation).

[0078] In some embodiments, the dispersant may be present in the epoxy resin composition in an amount of at least 0.1, 0.2, 0.3, or 0.4 wt % and up to 10 wt %, based on the total weight of the epoxy resin composition, hi some embodiments, the amount of dispersant is no more than 9, 8, 7, 6, 5, 4, 3, or 2 wt %.

[0079] In some embodiments, the dispersant may be premixed with the thermally conductive particles prior to incorporation into the (e.g., epoxy resin and / or epoxy-reactive) organic components. Such premixing may facilitate the uncured epoxy resin composition to be Newtonian or enable shear thinning behavior.

[0080] The epoxy composition may further optionally contain various additives, such as antioxidants / stabilizers, colorants, abrasive granules, thermal decomposition stabilizers, light stabilizers, conductive particles, tackifiers, flow agents, thickeners, matting agents, non-conductive fillers, binders, foaming agents, fungicides, bactericides, surfactants, plasticizers, and other additives known to those skilled in the art. When present, these additives are added in amounts effective for their intended purpose. The total amount of such additives is generally no more than 10, 9, 8, 7, 6, 4, 3, 2, 1.5, 1, or 0.5 weight percent of the total epoxy resin composition.

[0081] In some embodiments, the curable composition may be provided (e.g., packaged) as a two-part composition, where a first part includes the epoxy resin and a second part includes the epoxy-reactive oligomer component and other epoxy-reactive components, such as a curing agent. When the oligomer component is a toughening agent, the toughening agent is typically combined with the epoxy resin.

[0082] Other components of the curable composition (e.g., additives such as thermally conductive particles, dispersants, catalysts, antioxidants, etc.) may be included in one or both of the first and second portions. In some embodiments, the curable composition is provided in a dispenser comprising a first chamber and a second chamber. The first chamber includes a first (e.g., epoxy resin) portion and the second chamber includes a second (e.g., epoxy reactive component) portion.

[0083] The inclusion of a relatively high concentration of thermally conductive particles can affect mechanical properties. The epoxy resin and oligomer components are selected to provide a cured epoxy resin composition that is particularly useful as an enclosure (e.g., a housing or case) for an electronic device.

[0084] In some embodiments, the cured epoxy resin composition has a strain at break of at least 1, 2, 3, 4, 5, 6, or 7% when measured according to ASTM D638 (as described in more detail in the Examples). The strain at break is typically less than the same epoxy resin composition without the thermally conductive particles (e.g., 20%). In some embodiments, the cured epoxy resin composition has a strain at break of 15% or 10% or less.

[0085] In some embodiments, the cured epoxy resin composition has an elastic modulus of at least 2, 3, 4, 5, 6, or 7 GPa, as measured according to ASTM D638 (as described in more detail in the Examples). In some embodiments, the cured epoxy resin composition has an elastic modulus of no more than 50, 45, 40, 35, 30, 25, 20, or 15 GPa.

[0086] In some embodiments, the cured epoxy resin composition is radio frequency transparent, and the cured epoxy resin is 4 ~10 10 It has a loss tangent of <0.03 for frequencies in the Hertz range.

[0087] In some embodiments, the cured epoxy resin composition has a gloss value, measured according to the test methods described in the examples, of at least 70, 75, 80, or 85. The gloss value is typically no greater than 95 or 90.

[0088] Any known molding method suitable for epoxy resin compositions can be used to form the curable epoxy resin composition into an enclosure. In one embodiment, the curable epoxy resin composition may be provided as a two-part composition. Generally, the two components of the two-part composition may be mixed before being formed into an enclosure, such as by feeding the epoxy resin composition into a mold.

[0089] In one embodiment, a transfer film is provided to the mold prior to providing the epoxy resin composition, the transfer film comprising a release liner, a transfer polymer layer disposed on the release liner, and a plurality of microspheres embedded in the transfer polymer layer. The method further comprises removing the release liner and the transfer polymer layer after curing the epoxy resin. Further details regarding making the transfer film and the finished molded article are described in U.S. Patent No. 62 / 552465, which is incorporated herein by reference.

[0090] Microspheres include glasses, glass-ceramics, ceramics, polymers, metals, and combinations thereof. Glasses are amorphous materials, while ceramics refer to crystalline or partially crystalline materials. Glass-ceramics have an amorphous phase and one or more crystalline phases. Such materials are known in the art.

[0091] In some embodiments, the microspheres are glass beads. The glass beads are mostly spherical. Glass beads are typically produced from recycled sources such as glazing and / or glass products, typically by crushing regular soda-lime or borosilicate glasses. Regular industrial glasses can be of various refractive indices depending on their composition. Soda-lime silicates and borosilicates are common types of glasses. Borosilicate glasses typically contain boria and silica, along with other elemental oxides such as alkali metal oxides and alumina. Some glasses used in the industry that contain boria and silica, among other oxides, include E-glass and glasses available under the trade name "NEXTERION GLASS D" from Schott Industries, Kansas City, Missouri, and glasses available under the trade name "PYREX" from Corning Incorporated, New York, New York.

[0092] In some embodiments, the microspheres are substantially spherical, e.g., have a sphericity of at least 80%, 85%, or even 90%, where sphericity is defined as the surface area of ​​a sphere (of the same volume as a given particle) divided by the surface area of ​​the particle, and is reported as a percentage.

[0093] The microspheres may be transparent, translucent, or opaque. In one embodiment, the microspheres have a refractive index of at least 1.4, 1.6, 1.8, 2.0, or even 2.2. The refractive index can be measured by the standard Becke line method.

[0094] In some embodiments, useful ranges of average microsphere diameters are at least 5, 10, 20, 25, 40, 50, 75, 100, or even 150 μm (micrometers) and up to 200, 400, 500, 600, 800, 900, or even 1000 μm. The microspheres can have a unimodal or multimodal (e.g., bimodal) size distribution depending on the application.

[0095] The inclusion of microspheres partially embedded in the cured epoxy resin can increase the pencil hardness. In one embodiment, the pencil hardness is at least 6K, 7H, 8H, 9H, or 10H. The pencil hardness is typically 10H or less.

[0096] The advantages and embodiments of the present disclosure are further illustrated by the following examples, in which the particular materials and amounts thereof, as well as other conditions and details, are not to be construed as unduly limiting the invention, and in which all percentages, proportions and ratios are by weight unless otherwise indicated. EXAMPLES

[0097] All parts, percentages, ratios, etc. in the examples and elsewhere in the specification are by weight unless otherwise noted. Unless otherwise noted, all other reagents were obtained or available from fine chemical commercial suppliers, such as Sigma-Aldrich Company (St. Louis, Missouri), or can be synthesized by known methods.

[0098] Abbreviations for materials used in the examples are listed in Table 1 below.

[0099] [Table 2]

[0100] Test Method Mechanical Testing - Elastic Modulus and Strain at Break All examples were prepared by thermally curing the resin in a glass mold. The glass mold was pretreated with a mold release agent, FREKOTE 55NC (Henkel, Dusseldorft, Germany), and dried three times before injecting the resin. The glass plates were separated by a rubber gasket material of appropriate thickness. A 1 / 8 inch (3.18 millimeters (mm)) thickness was used for the tensile and DMA specimens. A plaque was cured at that thickness with dimensions of approximately 6 inches by 8 inches (15.24 centimeters (cm) by 20.32 cm). From this plaque, six tensile specimens were cut at 4.5 inches by 0.75 inches (11.43 cm by 1.91 cm) and trimmed to 0.25 inch (6.35 mm) gauge sections using a router to produce specimens conforming to ASTM D638 Type IV geometry. These samples were tested in tension at a displacement rate of 5 mm / min on an MTS Insight (Eden Prairie, MN) load frame equipped with an extensometer and load cell to obtain the load displacement, and finally the elastic modulus and average strain at break are reported in Table 4.

[0101] The cured resin density was determined by measuring the mass of a sample in air and measuring the mass of the same sample submerged in heptane. The density was then calculated based on Archimedes' principle.

[0102] Thermal Conductivity Cured resin disks approximately 12.7 mm in diameter and 2 mm thick were prepared by curing the resin in a 12.7 mm diameter vial. The vial was treated with a mold release agent (FREKOTE 55NC). After curing, the resin was removed from the vial and cut into 2 mm thick disks for laser flash analysis (LFA), as described below.

[0103] Direct thermal diffusivity measurements were performed using the flash analysis method according to ASTM E1461 (2013) using a light flash thermal property analyzer ("HYPERFLASH LFA 467" obtained from Netzsch Instruments North America LLC, Boston, MA). All sample sets included a reference sample (obtained from Netzsch Instruments North America under the trade designation "PYROCERAM 9606") to serve as a control method for the diffusivity measurements. The light impingement and detection sides of the samples were coated with a sprayed layer of 3-5 micrometer graphite (obtained from Miracle Power Products Corporation, Cleveland, OH under the trade designation "DGF 123 DRY GRAPHITE FILM SPRAY") to normalize the surface permeability and absorptivity for all samples. In a single measurement, called a "shot", a short duration pulse of light (Xenon flash lamp, 230 V, 15 microsecond duration) was impinged on one side of the sample, as measured by the voltage on the InSb Ir detector, and a thermogram (time trace of the measured temperature) was recorded on the other side of the sample. The diffusivity was calculated by fitting the thermogram to a Cowan + pulse correction model for the thickness direction. The through-plane diffusivity was calculated using the Cowan method plus finite pulse width correction, and the in-plane diffusivity used an isotropic model with the help of software (obtained under the trade name "Proteus" from Netzsch, Selb, Germany). Five shots were obtained for each sample at 25°C. The thermal conductivity is the product of the measured density (geometric density from a 2.54 cm (1 inch) disk), the specific heat capacity (by differential scanning calorimeter), and the diffusivity: i.e.

number

[0104] Dynamic Mechanical Analysis (DMA) The glass transition temperature was determined from the tan(δ) peak of the elastic modulus measured by DMA. Samples were prepared with dimensions of 1.7 mm×12.7 mm×30 mm and mounted in a single cantilever fixture with a span of approximately 20 mm. The samples were tested in single cantilever mode with a deflection of 20 μm at a frequency of 10 Hz to measure the storage modulus (E′) and loss modulus (E”). The tan(δ) values ​​were calculated. tan(δ)=E” / E' The measurements were performed at a temperature ramp rate of 3°C / min from 0°C to 175°C. The reported glass transition temperatures (T g ) is the temperature at maximum tan(δ).

[0105] When the cured epoxy resin composition has at least two glass transition temperatures, the cured Tg is defined as the ultimate Tg or tan δ transition of highest strength, which may be the highest temperature transition.

[0106] Gloss Measurement 3 inch x 3 inch x 1 / 8 inch (7.62 cm x 7.62 cm x 3.18 mm) specimens were cut from the plaques and used to measure gloss as a function of particle size. Gloss measurements (Table 5) were made on molded samples using a BYK Spectroguide Glossmeter (product number 6834, BYK Additives and Instruments, Wesel, Germany). The glossmeter measured at an angle of 60°. High gloss materials were defined as having values ​​greater than 70 gloss units (GU).

[0107] pencil hardness The pencil hardness of the specimens was evaluated according to ASTM D3363-5 05(2011)e2. Abrasive paper (grit no. 400) was attached to a flat, smooth bench top with double-sided tape. Pencil leads (Turquoise Premium pencil leads (hardness 10H-6B)) from Prismacolor Professional Art Supplies, a subsidiary of Newell Rubbermaid Office Products (Oak Brook, IL) were used. The pencil leads were held at a 90° angle to the abrasive paper with a mechanical lead holder (TOTIENS 210 99 from Cretacolor (Hirm, Austria)) and abraded until a flat, smooth, circular cross section was obtained, free of chips or nicks at the edge of the lead. The force at the tip of the pencil was fixed at 7.5 Newtons (N) or in some cases fixed at a smaller value. Using a freshly prepared pencil lead for each test, an Elcometer 3086 Powered Pencil Hardness Tester (Elcometer Incorporated, Rochester 15 Hills, Mich.) was used to firmly press the lead against the piece at a 45° angle and the desired load to draw a line at least 1 / 4 inch (6.4 mm) long in the "forward" direction across the test panel. Three pencil lines were made for each grade of lead hardness. Prior to testing, any broken lead was removed from the test area using a damp paper towel moistened with isopropyl alcohol. The test panels were inspected visually for defects and under a light microscope (50X to 1000X magnification) for the first 1 / 8 to 1 / 4 inch (3.2 to 6.4 mm) of each pencil track. The above process was repeated going down the hardness scale from harder to softer leads until a pencil was found that did not scratch or tear the film or cause any of the microspheres to fall off or partially fall off. At least two of the three lines of each lead hardness had to meet these criteria to pass. The hardness of the hardest lead that passed was recorded as the pencil hardness for that test panel. A hardness value of 3H or greater at a force of 5 Newtons is desirable.

[0108] RF Permeability Dielectric Constant and Loss Tangent Measurement The terms "dielectric constant", "dielectric loss", and "loss tangent" are used consistent with their commonly understood definitions. Dielectric constant (at any frequency) is the amount of energy stored per cycle of electric field oscillation and is determined as the real part of the complex permittivity defined by Maxwell's equations. Dielectric loss (at any frequency) is the amount of energy dissipated per cycle of electric field oscillation and is determined as the imaginary part of the complex permittivity defined by Maxwell's equations. Loss tangent (at any frequency) is the ratio of dielectric loss to dielectric constant.

[0109] Dielectric property measurements up to 1 MHz were performed using an Alpha-A High Temperature Broadband Dielectric Spectrometer modular measurement system from Novocontrol Technologies (Montabaur, Germany). All tests were performed according to the ASTM D150 test standard. Some of the films were painted with copper paint and some were laminated directly onto the brass electrodes without copper paint, depending on how well the sample could conform to the electrode surface. Each sample was placed between two optically polished brass disks (40.0 mm in diameter and 2.00 mm thick) and a Novocontrol ZGS Alpha Active Sample Cell was performed.

[0110] Dielectric property measurements above 1 MHz were performed using three separate split-post dielectric resonators at 2.5 GHz, 5.6 GHz, and 9.5 GHz, respectively. All measurements above 1 MHz were performed according to standard IEC 61189-2-721.

[0111] Refractive index measurement (Becke line method) A set of predetermined refractive index test liquids available from Cargille of Cedar Grove, New Jersey, was used to determine the refractive index of the transparent microspheres using the procedure described below.

[0112] A sample of a transparent microsphere was placed on a microscope slide and a drop of the test liquid was placed in contact with the sample and covered with a coverslip. The microscope was adjusted to focus on the bead. Once in focus, the focuser was used to lower the microscope stage and a bright line was observed on the outline of the microsphere as the focus changed. If the bright line moved outward into the liquid as the stage was lowered, the liquid had a higher refractive index than the bead. On the other hand, if the bright line moved into the bead, the refractive index of the microsphere was higher. By testing a series of liquids with different refractive indices, the approximate refractive index of the microsphere was identified. When two liquids were present on either side of the refractive index of the microsphere, an interpolation of the true value was made.

[0113] Examples and Comparative Examples The materials in Table 1 were used as received unless otherwise noted. The weight percentages of the components are listed in Table 2 (inorganic inclusions and dispersants) and Table 3 (curable organic resins). The volume percentages of thermally conductive particles (vol.%) were calculated based on the mass of the input materials, assuming an alumina particle density of 3.9 grams per cubic centimeter (g / cc), an aluminum trihydrate (ATH) particle density of 2.2 g / cc, and a resin density of 1.15 g / cc.

[0114] [Table 3]

[0115] [Table 4]

[0116] Comparative Examples (CE) 1 and 2 are representative unfilled epoxy resins. Without the incorporation of oligomer diol, CE1 was very brittle and could not be machined into tensile samples. In representative Comparative Example 1, 90 grams (g) of cycloaliphatic ester (L190), 60 g of C2054, and 3.75 g of CXC-1612 were combined in a 300 g capacity Speed ​​Mix cup (FlackTek Inc., Landrum, SC). The ingredients were speed mixed under atmospheric conditions in a DAC600 VAC mixer (FlackTek Inc.) at 2200 revolutions per minute (rpm) for 30 seconds, followed by vacuum degassing while speed mixing at 800 rpm for 3 minutes. The final pressure reached under vacuum was approximately 10 millibar (mbar). CE2 was mixed and degassed in the same manner using the resin amounts consistent with Table 3.

[0117] The cure cycle for CE1, Ex1, and any examples cured with CXC-1612 was 30 minutes at 80° C., followed by 60 minutes at 120° C. The cure cycle for CE2 and any materials cured with NBDA was 1 hour at 80° C. After curing, the resin plaques were cooled to room temperature, demolded, and cut into appropriate geometric shapes as described in the Mechanical Testing—Modulus and Strain at Break section.

[0118] All Ex3-Ex9 were similarly processed with weight ratios of ingredients consistent with Tables 2 and 3. In representative Example 3, 240 g of AX1M alumina particles were combined with 1.2 g of B9012 in a FlackTek Speed ​​Mix cup and speed mixed in a DAC600.2 VAC mixer (FlackTek Inc.) at 1500 rpm for 30 seconds. Then, 1.5 g of CXC-1612, 33.2 g of L190, and 24.1 g of C2054 were added to the Speed ​​Mix cup, followed by speed mixing at 2200 rpm for 30 seconds under atmospheric conditions and vacuum degassing while speed mixing at 800 rpm for 3 minutes. The pressure reached under vacuum was approximately 10 mbar. After mixing, the resin was flowable but not completely deagglomerated, so it was passed through a three-roll mill equipped with ceramic rollers (Exakt Technologies Inc., Model 50 I) to deagglomerate. A final mixing and degassing step was applied at 800 rpm with vacuum pressure reduced to 10 pounds per square inch (psi), or 0.069 megapascals (MPa). The mixed and degassed resin was poured into release treated glass molds and cured at 80°C for 30 minutes, followed by 120°C for 1 hour. After curing, the resin plaques were cooled to room temperature, demolded, and cut into the appropriate geometric shapes as described below. The same procedure and cure cycle was used for Ex3-Ex9.

[0119] CE3 and Ex2 consisted of the epoxy resin described in CE2, filled with a thermally conductive filler. Alumina particles were mixed separately into the epoxy and hardener (NBDA) components. Both the epoxy and hardener contained alumina particles at weight percents equal to the total weight percents in Table 3. For representative Ex2, 209 g of AX1M alumina particles were speed mixed with 1.04 g of B9012 in a 300 g Speed ​​Mix cup at 1500 rpm for 30 seconds. To this cup, 28 g of Bis-A epoxy and 24 g of chain extended epoxy (E4850) were added and the mixture was speed mixed and passed through a 3-roll mill as above. In a separate 200 g Speed ​​Mix cup, 31 g of AX1M alumina particles were combined with 0.15 g of B9012 and speed mixed at 2200 rpm for 30 seconds. Then, 7.9 grams of NBDA (hardener) were added and speed mixed at 2200 rpm for 30 seconds. The alumina filled epoxy and alumina filled hardener were combined in a single 300 g Speedmix cup and vacuum degassed at 800 rpm for 3 minutes until a vacuum pressure of 10 mbar was reached. The mixed resin was poured into a release agent treated glass mold and cured at 80°C for 1 hour. CE3 was prepared by the same procedure as Ex3-Ex9 using the amounts listed in Tables 2 and 3. Ex10 was the epoxy resin composition from Ex4 with a borosilicate glass bead surface to improve hardness and scratch resistance.

[0120] Borosilicate glass powder was passed twice through a flame treater by passing it through a hydrogen / oxygen flame at a rate of 3 grams / minute to form microspheres, which were collected in a stainless steel container and removed from metal impurities using a magnet. The resulting glass microspheres were treated with 600 ppm A1100 in the following manner: Silane was dissolved in water and then added to the microspheres with mixing, air-dried overnight, and then dried at 110° C. for 20 minutes. The dried silane-treated microspheres were then sieved to remove any agglomerates to yield free-flowing microspheres 75 μm or less in size. The resulting transparent silane-treated microspheres were cascade coated using a mechanical sifter onto a transfer carrier film comprising 25 μm (0.0010 in) low density polyethylene coated on a 97 μm (0.0038 in) polyester release liner, preheated to approximately 140° C. (284° F.), to form a bead carrier having a uniform layer of transparent microspheres embedded in the low density polyethylene layer to a depth corresponding to approximately 30-40% of their diameter as determined by a magnification imaging system.

[0121] A 200m x 200mm (7.9" x 7.9") section of the transfer film with the embedded borosilicate beads was adhered with the beaded side facing inwards to the inside surface of one of the glass molds (having a cavity of 200mm x 250mm x 3mm) so that when the mold was filled with the epoxy resin composition, the borosilicate beads would contact and be partially embedded in the epoxy resin composition. The mold was filled with the resin described in Ex4. The epoxy, beaded surface, and mold were heated in an oven at 90°C for 1 hour to gel the epoxy. The mold was disassembled and the polyester release liner was removed from the silicate beads along with the low density polyethylene, leaving the beaded borosilicate surface on the epoxy resin. This was cured at 120°C for 1 hour. Ex10 was mechanically tested for tensile and pencil hardness as described above and the results are included in Tables 4 and 6, respectively.

[0122] [Table 5]

[0123] [Table 6]

[0124] [Table 7]

[0125] [Table 8]

[0126] Example 11 In a FlackTek Speed ​​Mix cup, 150.3 grams of AX1M alumina particles were combined with 48.77 grams of Syna Epoxy 21, 19.11 grams of C2054, and 4.81 grams of C3031 and speed mixed in a DAC 600.2VAC mixer (FlackTek Inc.) at 2000 rpm for 30 seconds. Then, 0.76 grams of BYK 9010 was added and the formulation was speed mixed at 2000 rpm for 30 seconds. The remaining 150.33 grams of AX1M alumina particles were then added along with 1.84 grams of CXC1612 and speed mixed at 2000 rpm for 30 seconds. After mixing, the resin was flowable but not completely deagglomerated, so it was passed through a three-roll mill with ceramic rollers (Exakt Technologies Inc., Model 50 I) to deagglomerate. A final mixing and degassing step using a DAC 600.2 was applied for 200 seconds with the vacuum pressure reduced to 10 pounds per square inch (psi). The mixed and degassed resin was poured into release treated molds and allowed to cure. After curing, the resin plaques were cooled to room temperature, demolded, and cut into the appropriate geometric shapes as described below.

[0127] Example 12 In a FlackTek Speed ​​Mix cup, 50.3 grams of AX1M alumina particles were combined with 16.735 grams of Syna Epoxy 21, 7.178 grams of C2054 and speed mixed in a DAC 600.2VAC mixer (FlackTek Inc.) at 2000 rpm for 30 seconds. Then, 0.498 grams of BYK 9010 was added and the formulation was speed mixed at 2000 rpm for 30 seconds. Then, the remaining 50.2 grams of AX1M alumina particles were added along with 0.6009 grams of CXC1612 and speed mixed at 2000 rpm for 30 seconds. After mixing, the resin was flowable but not completely deagglomerated, so it was passed through a three-roll mill with ceramic rollers (Exakt Technologies Inc., Model 50 I) to deagglomerate. A final mixing and degassing step using a DAC 600.2 was applied for 200 seconds with the vacuum pressure reduced to 10 pounds per square inch (psi). The mixed and degassed resin was poured into release treated molds and allowed to cure. After curing, the resin plaques were cooled to room temperature, demolded, and cut into the appropriate geometric shapes as described below.

[0128] Example 13 In a FlackTek Speed ​​Mix cup, 50.2 grams of AX1M alumina particles were combined with 17.925 grams of Syna Epoxy 21, 5.958 grams of C2054 and speed mixed in a DAC 600.2VAC mixer (FlackTek Inc.) at 2000 rpm for 30 seconds. Then, 0.4968 grams of BYK 9010 was added and the formulation was speed mixed at 2000 rpm for 30 seconds. Then, the remaining 49.95 grams of AX1M alumina particles were added along with 0.5974 grams of CXC1612 and speed mixed at 2000 rpm for 30 seconds. After mixing, the resin was flowable but not completely deagglomerated, so it was passed through a three-roll mill with ceramic rollers (Exakt Technologies Inc., Model 50 I) to deagglomerate. A final mixing and degassing step using a DAC 600.2 was applied for 200 seconds with the vacuum pressure reduced to 10 pounds per square inch (psi). The mixed and degassed resin was poured into release treated molds and allowed to cure. After curing, the resin plaques were cooled to room temperature, demolded, and cut into the appropriate geometric shapes as described below.

[0129] Example 14 In a FlackTek Speed ​​Mix cup, 49.98 grams of AX1M alumina particles were combined with 18.082 grams of Syna Epoxy 21, 6.041 grams of C2054 and speed mixed in a DAC 600.2VAC mixer (FlackTek Inc.) at 2000 rpm for 30 seconds. Then, 0.2516 grams of BYK 9012 were added and the formulation was speed mixed at 2000 rpm for 30 seconds. Then, the remaining 50.2 grams of AX1M alumina particles were added along with 0.6033 grams of CXC1612 and speed mixed at 2000 rpm for 30 seconds. After mixing, the resin was flowable but not completely deagglomerated, so it was passed through a three-roll mill with ceramic rollers (Exakt Technologies Inc., Model 50 I) to deagglomerate. A final mixing and degassing step using a DAC 600.2 was applied for 200 seconds with the vacuum pressure reduced to 10 pounds per square inch (psi). The mixed and degassed resin was poured into release treated molds and allowed to cure. After curing, the resin plaques were cooled to room temperature, demolded, and cut into the appropriate geometric shapes as described below.

[0130] Example 15 In a FlackTek speed mix cup, 62.26 grams of AX1M alumina particles were combined with 18.5228 grams of Syna Epoxy-21, 11.365 grams of C2054 and speed mixed in a DAC 600.2VAC mixer (FlackTek Inc.) at 2000 rpm for 30 seconds. Then, 0.6224 grams of BYK 9012 were added and the formulation was speed mixed at 2000 rpm for 30 seconds. Then, the remaining 62.25 grams of AX1M alumina particles were added along with 0.7473 grams of CXC1612 and speed mixed at 2000 rpm for 30 seconds. After mixing, the resin was flowable but not completely deagglomerated, so it was passed through a three-roll mill with ceramic rollers (Exakt Technologies Inc., Model 50 I) to deagglomerate. A final mixing and degassing step using a DAC 600.2 was applied for 200 seconds with the vacuum pressure reduced to 10 pounds per square inch (psi). The mixed and degassed resin was poured into release treated molds and allowed to cure. After curing, the resin plaques were cooled to room temperature, demolded, and cut into the appropriate geometric shapes as described below.

[0131] Example 16 In a FlackTek Speed ​​Mix cup, 50.05 grams of AX1M alumina particles were combined with 16.039 grams of Syna Epoxy-21, 7.89 grams of C2054 and speed mixed in a DAC 600.2VAC mixer (FlackTek Inc.) at 2000 rpm for 30 seconds. Then, 0.4991 grams of BYK 9012 were added and the formulation was speed mixed at 2000 rpm for 30 seconds. Then, the remaining 50.15 grams of AX1M alumina particles were added along with 0.5952 grams of CXC1612 and speed mixed at 2000 rpm for 30 seconds. After mixing, the resin was flowable but not completely deagglomerated, so it was passed through a three-roll mill with ceramic rollers (Exakt Technologies Inc., Model 50 I) to deagglomerate. A final mixing and degassing step using a DAC 600.2 was applied for 200 seconds with the vacuum pressure reduced to 10 pounds per square inch (psi). The mixed and degassed resin was poured into release treated molds and allowed to cure. After curing, the resin plaques were cooled to room temperature, demolded, and cut into the appropriate geometric shapes as described below.

[0132] [Table 9]

Claims

1. an enclosure that is a housing or case, the housing or case comprising a cured epoxy resin composition that includes at least 50 volume percent electrically non-conductive, thermally conductive inorganic particles; The cured epoxy resin composition is radio-frequency transparent, and the cured epoxy resin composition is 4 ~10 10 Hz range, has a dielectric loss tangent of <0.03; An electronic device selected from a phone, a tablet, a laptop, or a mouse.

2. 10. The electronic device of claim 1, wherein the cured epoxy resin composition comprises a plurality of microspheres partially embedded in the cured epoxy resin composition.

3. 3. The electronic device of claim 2, wherein the cured epoxy resin composition including the plurality of microspheres partially embedded therein has a pencil hardness of greater than 6H.

4. The electronic device according to any one of claims 1 to 3, wherein the cured epoxy resin composition has a thermal conductivity of at least 1 W / m·K.

5. The electronic device of any one of claims 1 to 4, wherein the non-conductive, thermally conductive inorganic particles comprise a material with an electronic band gap >0 eV.

6. The electronic device of any one of claims 1 to 5, wherein the electronic device comprises a battery that can be charged via the cured epoxy resin composition of the enclosure.

7. The electronic device of any one of claims 1 to 6, wherein the non-electrically conductive, thermally conductive inorganic particles comprise a material having a bulk thermal conductivity of >10 W / m·K.

8. The electronic device according to any one of claims 1 to 7, wherein the non-electrically conductive, thermally conductive inorganic particles are selected from alumina, boron nitride, silicon carbide, alumina trihydrate, and mixtures thereof.

9. The electronic device of any one of claims 1 to 8, wherein the non-conductive, thermally conductive inorganic particles have a median particle size of less than 20, 10, 5, or 1 micron.

10. The electronic device of any one of claims 1 to 9, wherein the cured epoxy resin composition comprises cyclic moieties.

11. The electronic device according to any one of claims 1 to 10, wherein the cured epoxy resin composition comprises 2 to 20 wt% of an oligomeric or polymeric moiety having a glass transition temperature below 0°C.

12. a first portion comprising an epoxy resin; a second part comprising 2-20 wt. % of an epoxy reactive oligomeric or polymeric moiety having a glass transition temperature below 0° C.; and an organic component comprising: at least 50% by volume of non-electrically conductive, thermally conductive, inorganic particles; An epoxy resin composition comprising: An epoxy resin composition, wherein the cured epoxy resin composition is radio frequency transparent and the cured epoxy resin composition has a dielectric loss tangent of <0.03 in the range of 10 4 to 10 10 Hz.

13. 13. The epoxy resin composition of claim 12, wherein the cured epoxy resin composition has a thermal conductivity of at least 1 W / m·K.

Citation Information

Patent Citations

  • Ultraviolet-curable organopolysiloxane composition

    JP1992159322A

  • Epoxy composition and epoxy resin molded article

    JP2014148579A

  • Curable epoxy resin composition

    WO2012091000A1